2014
DOI: 10.1002/jms.3358
|View full text |Cite|
|
Sign up to set email alerts
|

Low C24‐OH and C22‐OH sulfatides in human renal cell carcinoma

Abstract: Histopathologic diagnosis of renal cell carcinoma (RCC) may sometimes be difficult with small biopsy samples. We applied histology-directed matrix-assisted laser desorption/ionization mass spectrometry to RCC samples to evaluate whether and how lipid profiles are different between RCC and normal tissue. We evaluated 59 RCC samples and 24 adjacent normal tissue samples collected from patients who underwent surgery. Five peaks were significantly differently expressed (p < 10(-7)) between RCCs and adjacent normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In our previous work, we compared 157 tumor and autologous nonmalignant tissues from 80 patients with RCC [19], and reported decreased concentrations of monohexosyl sulfatides (SHexCer) with additional hydroxyl in the ceramide part in the tumor tissue compared to non-neoplastic autologous tissue. These observations are consistent with the results reported by Kim et al [14]. We found elevated levels of sulfatides composed of two hexosyl units (SHex2Cer) in tumor tissues compared to adjacent nonneoplastic tissues.…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our previous work, we compared 157 tumor and autologous nonmalignant tissues from 80 patients with RCC [19], and reported decreased concentrations of monohexosyl sulfatides (SHexCer) with additional hydroxyl in the ceramide part in the tumor tissue compared to non-neoplastic autologous tissue. These observations are consistent with the results reported by Kim et al [14]. We found elevated levels of sulfatides composed of two hexosyl units (SHex2Cer) in tumor tissues compared to adjacent nonneoplastic tissues.…”
Section: Introductionsupporting
confidence: 94%
“…Sulfatides participate in adhesion to functional proteins, the maintenance and modification of ion channels, and the induction of cell differentiation [13]. The importance of sulfatide metabolism and sulfotransferase gene expression for the morphological differentiation of tumor and metastatic potentials of colorectal, ovarian, or renal carcinomas has been shown in numerous reports [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shotgun lipidomics based on electrospray ionization mass spectrometry (ESI-MS) allows deep molecular profiling of a sample without significant losses of chemical information [26,27]. The high diagnostic potential of lipidomics has been shown in many areas of medicine, particularly in oncology: lung, thyroid gland, breast, stomach, pancreas, colorectal, liver, kidney, prostate, ovarian, and endometrium cancer [28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][51][31][32][33][34][35][36][37]. MS studies of lipid profiles in tissues and blood plasma have revealed new promising biomarkers of endometriosis (benign gynecological disorder) [26,27,32,33,37,44,47].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Several studies have proposed that disturbances in sulfatide metabolism might be associated with such kidney diseases as renal cell carcinoma and polycystic kidney disease. 13,14 Sulfated glycans, currently explored in medicine as glycosaminoglycans (GAGs), are also known to contribute to numerous pathophysiological processes. In the nervous system, GAGs reportedly play many critical roles, including regulation of the proliferation and differentiation of neural progenitor cells, neuronal migration, neural regeneration and plasticity, synaptogenesis, and axon pathfinding.…”
Section: Introductionmentioning
confidence: 99%